(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
BG-11 in the articlein nutrient mediaB. braunii-AnDI-115 andCh. infusionum-from the study of the effect of AnDI-76 strains on growth, biomass and pigment formation in relation to dry matterconsists.